Build a harmonious relationship through mindful self-compassion counseling student’s - Wiwied Widiyanti; Ummah Karimah; Hendriadi Hendriadi; Mariatul Hikmah (Konselor, 2021)
Harmonious relationship as an internal process that is in the mind can be done with prayer and contemplation that brightens life and gives self-awareness and can be a balanced healer. Mindful self-compassion counseling based on Islam contains actual programs that use mindfulness to gain love, acceptance, and forgiveness with contemplation (meditation) that uses Islamic values. The benefits of mindful self-compassion counseling based on Islam can be seen from several aspects, namely psychological, physiological, and sociological aspects. Where not only used for healing but also to help improve human spirituality to Allah SWT. This research is quasi-experimental research using the experimental group and the control group. Respondents consisted of 10 students of STAI Nurulfalah Airmolek who were divided into two groups (control and experiment). The research instrument to measure the harmonious relationship uses a harmonious relationship questionnaire which is part of the spiritual welfare instrument. This study aims to prove the effectiveness of Islamic-based mindful self-compassion counseling in building harmonious relationships. The results showed that Islamic-based mindful self-compassion counseling was effective enough to build a harmonious relationship with an N-Gain score of 60.82%.